UNREVEALING THE CHALLENGES OF NOVICE ENGLISH TEACHERS IN ENGLISH TEACHING - Azmi Nurlatifah; Rajji K. Adireja; Wahid Hasim (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This study aims to unrevealing the challenges of novice English teachers in English teaching. This research was used qualitative method. The writer used the case study design. The instrument for collecting the data through interviews. This study was conducted in some junior high school in Garut areas, West Java. It is located around rural area. The participants were selected utilizing the purposive sampling method. The findings showed that novice English teachers have some challenges in English teaching. First, novice teachers were difficulty implemented their knowledge in the world of work. Second, the biggest challenge for novice teachers is classroom management. Third, failure to manage the classroom caused students misbehavior in the classroom, such as daydreamed, slept in class, talked, used a smartphone, etc. Fourth, mentality, novice teachers often lead to childish attitudes when they were taught. Fifth, novice teachers thought about keep staying or leaving their profession as teachers. Sixth, all of the novice teachers felt sad and disappointed faced many problems.